2007
DOI: 10.1007/s00404-007-0418-1
|View full text |Cite
|
Sign up to set email alerts
|

Sexual function after surgery for stress urinary incontinence: vaginal sling versus Burch colposuspension

Abstract: Our findings show that sexual functions may be impaired after surgery for SUI. Burch colposuspension may deteriorate sexual functions much more than vaginal sling surgery in women. Therefore, women who will need surgery for SUI should be informed of the risk of deterioration of sexual function after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 29 publications
1
20
1
Order By: Relevance
“…In our study, TOT was found more superior over Burch operation in providing SUI. Although there are some studies supporting the results of our study in the literature (21,22), a study showed that Burch colposuspension surgery is more successful than TOT operation (23).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In our study, TOT was found more superior over Burch operation in providing SUI. Although there are some studies supporting the results of our study in the literature (21,22), a study showed that Burch colposuspension surgery is more successful than TOT operation (23).…”
Section: Discussionsupporting
confidence: 62%
“…In a prospective study by Cayan et al comparing the effects of Burch colposuspension and vaginal sling procedures on the sexual functions of women, more reduction was detected in FSFI scores in Burch colposuspension group compared to vaginal sling group (21). In a multicentric and prospective study by Filacamo et al evaluating the effects of mid-urethral sling operations (transobturator procedure and retropubic procedure) on the sexual functions of women and including the patients with urodynamic stress urinary incontinence and sexually inactive patients, a significant increase was observed in total FSFI and sub-area scores of all patients.…”
Section: Discussionmentioning
confidence: 98%
“…Generally, sexual function may be impaired after surgery for stress urinary incontinence. Cayan [9] found that Burch colposuspension deteriorated sexual function much more than vaginal surgery in women, but impact in the vaginal group was evident as well. Shah [10] was unable to show deterioration of sexual function in a series of 29 patients who underwent polypropylene sling insertion for urinary stress incontinence.…”
Section: Discussionmentioning
confidence: 97%
“…However, Cayan et al [24] found that while TSF scores improved significantly after vaginal slings and Burch colposuspension (P=0.00), women who underwent Burch procedure experienced worse sexual functions scores than those who underwent vaginal sling surgery. Statistically significant decreases in TSF scores, postoperative sexual desire (P=0.014), arousal (P=0.026), lubrication (P=0.004), and orgasm scores (P=0.008) were observed in the Burch group compared to the vaginal sling group.…”
Section: Impact Of Treatment For Stress Urinary Incontinence On Femalmentioning
confidence: 92%